Continuous and time-lapse magnetotelluric monitoring of low volume injection at Rittershoffen geothermal project, northern Alsace – France. (January 2018) - Abdelfettah, Y.; Sailhac, P.; Larnier, H.; Matthey, P.-D.; Schill, E.
Highlights: Quasi-continuous monitoring of geothermal fluid injection using magnetotelluric. Rittershoffen geothermal experiment monitored by magnetotelluric. Influence of the geomagnetic field intensity on magnetotelluric monitoring. Phase tensor analysis applied to Rittershoffen geothermal boublet. Abstract: An increasing interest in magnetotelluric monitoring of hydraulic stimulation experiments and of natural earthquakes currently requires a detailed investigation of the limits of this method. Our study contributes to this discussion with a unique quasi-continuous and long-term magnetotelluric monitoring of different injection and production experiments at the Rittershoffen geothermal site in Alsace (France). Here, we provide a first evaluation of the data and an outlook on more specific challenges. The geothermal doublet at Rittershoffen is operated through two wells GRT1 and GRT2. The magnetotelluric monitoring covers the end of drilling phase of GRT2, mostly, production from, but also injection into this well, injection into GRT1 and a circulation experiment. Magnetotelluric data were processed successfully using remote referencing. Transfer functions show particular variation pattern for different operations, i.e. an increase in uncertainty, conductivity and phase during test operation with a preferential direction sub-parallel to Shmin, i.e. perpendicular to the expected extension of the fractures controlling the reservoir. In particular fluid injection, either into GRT2 or GRT1 causes a strong decrease in resistivity by up to one order of magnitude in the YX component between about 8–25 s of period. However, the comparison between the temporal distribution of the occurring anomalies and the magnetic field intensity reveals an amplifying effect on the anomalies. In conclusion, we confirm earlier findings on the influence of the magnetic field intensity on magnetotelluric monitoring and at the same time show the lower limit of monitoring in particular monitoring of injection into deep geothermal reservoirs.